Perceptions and acceptance of lesbians and gay men among adolescents from a selected high school in Quezon City - Cabrera, Alaia Kimberly Bondoc; Tanada, Jodie Rose G.; Agustin, Estrella R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The study probes on adolescents' perception and acceptibility of lesbians and gay men. It focused on two variables, namely, biological make-up and exposure that influence adolescents' perception and acceptability of lesbians and gay men. Through the administration of a revised version of Dr. Gregory Herek's Attitudes Toward Lesbians and Gay Men scale to three classes of Grade 10 students from a selected school in Quezon City, the researchers were able to determine adolescent's attitudes toward lesbians and gay men, which also reflects their acceptability of the said genders. A follow-up face-to-face interview was done to determine their perception of the said gender deviations. Results yielded that there is a difference in the perceptions of lesbians and gay men. Furthermore, although the results revealed that there was not enough evidence to show the correlation of respondents' biological make-up and exposure to their attitudes toward lesbians and gay men, data from the interview yielded male adolescents being more acceptable of lesbians than gay men while female adolescents regarded gay men as more acceptable than lesbians. Although some respondents said that personally knowing lesbians and gay men made them more accepting of these gender deviations, some respondents held positive attitudes toward lesbians despite not personally knowing anyone. The researchers found out that there is a higher level of positive attitudes toward lesbians than gay men.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Lesbians -- Philippines; Gay men -- Philippines; Homosexuality -- Philippines